SALES ADMINISTRATION SYSTEM HOUSEHOLD GOODS IN CASH AT PT. VIENDORA CIPTA MANDIRI USING MICROSOFT VISUAL FOXPRO 9.0. - Hadi Purnomo (Jurnal Sistem Informasi, 2006)
The increasing administrative activities at the PT.Viendora Cipta Mandiri and the growing need for a wide range of information the writer trying to help create a system of sales at this company. At a sales system that has not been using the applications allow a user in processing data that was entered previously, will make the system slow, errors caused by wrong calculation or because of different data transfer with the input. By using the proposed sale of applications, especially for payment by cash, incoming data is expected to be in accordance with the expected output, so that the mistakes that usually occur can be suppressed to a minimum and the process was much faster. With the new computerized system, expected flow of information can move faster so that the efficiency and effectiveness of the work can be achieved to the maximum extent possible